Making markets work for people, climate, and nature: applied development economics for biodiversity conservation and climate change - Hilton, Thomas, author; Salerno, Jonathan, advisor; Jones, Kelly, committee member; Bruyere, Brett, committee member; Seidl, Andrew, committee member (Colorado State University. Libraries, 2025)
Climate change and biodiversity loss are being driven by unsustainable human behavior underpinned by market incentives and economic growth models that fail to adequately value nature. If global goals relating to people, climate, and nature are to be achieved, ambitious integrated approaches are required drawing on best practice from the conservation and development fields, pursuing transformational change in complex social-ecological systems, and directing scarce resources to their most cost-effective use. This dissertation contributes evidence in support of these objectives, applying tools and frameworks from the economic development field to global challenges of biodiversity loss and climate change. Manuscript 1 outlines a framework for integrated conservation and development programming rooted in complex systems thinking, Green Market Systems Development, drawing on the lessons from Manuscript 2 and a wider collaboration between practitioners in both fields. Manuscript 2 features an evaluation of livelihoods programming in conservation projects, comparing the approaches of recent projects funded through the UK government's Darwin Initiative and Illegal Wildlife Trade Challenge Fund with the gold standard of "Market Systems Development" programming in the economic development field. We find most conservation projects to adopt outdated models of direct aid delivery that fall short of best practice in the economic development sector. Manuscript 3 uses a cost-benefit analysis of a wildlife corridor in Tanzania to demonstrate how economic decision tools can help to allocate conservation funds to maximize conservation outcomes per dollar spent.